Model Service Life Skills Counselling (Life Skills Mentoring) Based Tri Hita Karana Citizens Group to Learn in the District Badung, Gianyar and Singaraja Bali Province - A.A. Ngurah Adhiputra (Mudra Jurnal Seni Budaya, 2010)
The study has been intended to develop life skills counselling models based on the tri hita karana concept is needed because counselling services in most society tend to be academic and vocationally oriented. Therefore, models of life skills counselling are obligatory. Four steps were taken in the study. First, preliminary overviews of general life skills education program in the society. Second, developing ‘hypothetical’ life skills counselling models based on the tri hita karana and formulating an early life skills counselling services. Third, conducting a model validation though seminars, and trying -out models and data analyses. At this stage, the researcher conducted data analyses between pre-test and post-test implementations. Fourth, based on the data analyses, the researcher formulated a final model of the Tri hita karana-based counselling service and further socialized, disseminated, and strengthened the places of counselling activities the in society. In general, this research has achieved the targeted goals; to develop a tri hita karana-based models in life skills counseling work. The model can be applied by tutors, technical resource persons, counselors, organizers of fasilitators at the Province of Bali.